2015
DOI: 10.1016/j.polymer.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of segmented pure polyurethane electrostriction behaviors based on their nanostructural properties

Abstract: Polyurethane (PU) exhibit very high electromechanical activity, and has a great interest for a wide range of transducer and actuator applications. It has been recently pointed out that this strong electrostriction may result from the phase separation. In the present work, a model taking account the PU nanostructure is presented. In order to validate this model, three PUs of similar compositions but different soft segment fractions have been characterized by DSC, TEM, AFM and SAXS and their electrostriction pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Alhough it is difficult to interpret fractured surfaces, as it depends how they were obtained, it is interesting to analyze the possible reason for these observations, which were done by the same person, operating in the same conditions for all the samples. First of all, it must be recalled that the phase‐separation process of block copolymers such as PU is very complex and is driven by macromolecular diffusion, which, in turn, depends on the solvent content and on different parameters like temperature, macromolecular weight of the polymeric chains, etc . Some authors have already shown that for a polymer–solvent mixture, steady evaporation drastically changes the demixing kinetics, giving rise to multiple length scales .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alhough it is difficult to interpret fractured surfaces, as it depends how they were obtained, it is interesting to analyze the possible reason for these observations, which were done by the same person, operating in the same conditions for all the samples. First of all, it must be recalled that the phase‐separation process of block copolymers such as PU is very complex and is driven by macromolecular diffusion, which, in turn, depends on the solvent content and on different parameters like temperature, macromolecular weight of the polymeric chains, etc . Some authors have already shown that for a polymer–solvent mixture, steady evaporation drastically changes the demixing kinetics, giving rise to multiple length scales .…”
Section: Resultsmentioning
confidence: 99%
“…Polymers offer several advantages in terms of flexibility, low cost, and easy processing into different shapes, which does not require high temperatures. Among the EAPs, thermoplastic polyurethanes (PUs) present a high electromechanical activity, and several studies have been conducted in view of their properties, for example, studies on different types of PU, the improvement of electromechanical performances with the incorporation of nanofillers, the determination of electrical and mechanical properties, etc . As a consequence, they can be used, for example, in the replacement of piezoelectric ceramics for microelectromechanical systems (MEMS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compositional development and advances continue to improve DEA performance. For example, Jomaa et al describe how the microphase separation that is predominant in PUs can be exploited to improve electrostriction by adjusting the electrical properties of the hard and soft domains (which have different dielectric constants) 170. In other words, the phase separation of the two domain types in PUs leads to heterogeneities of both elastic and dielectric constants which contribute to the performance of the DEA.…”
Section: Dielectric Elastomersmentioning
confidence: 99%
“…To answer these questions, we start to search for alternative electrostrictive polymers and understand the fundamental mechanism. Recently, certain thermoplastic polyurethanes (PUs) were reported to demonstrate electrostrictive property because their electro‐actuation was significantly larger than that predicted by the Maxwell pressure . Meanwhile, even‐numbered nylon homopolymers and random copolymers based on nylon‐12 exhibited narrow double hysteresis (i.e., paraelectric) and single hysteresis (i.e., RFE behavior) loops, respectively, above the glass transition temperature ( T g ) .…”
Section: Introductionmentioning
confidence: 99%